Scanner-generated native T1 mapping: a novel approach for assessing myocardial fibrosis in coronary heart disease - Kong, Li; Tian, Xiaohong; Ji, Bing; Wang, Jian; Liang, Hongqin; Ji, Xiaojuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTo investigate the feasibility of using native longitudinal relaxation time (T1) mapping values, derived from the Picture Archiving and Communication System (PACS), for assessing diffuse myocardial fibrosis in patients with coronary heart disease (CHD).Materials and methodsPatients with CHD group were retrospectively enrolled as the experimental group, while age- and sex-matched healthy individuals were included as the control group. Based on the results of late gadolinium enhancement (LGE) sequence from cardiac magnetic resonance (CMR) imaging, the CHD group was further stratified into two subgroups: the LGE positive group (LGE+) and the LGE negative group (LGE−). The correlation between native T1 values and extracellular volume (ECV) values were assessed using the Pearson correlation coefficient.ResultsA total of 60 patients with coronary heart disease (age 54.03 ± 9.86 years) were included in the analysis, of whom 30 had late gadolinium enhancement (LGE+) and 30 did not (LGE−). The control group consisted of 42 healthy subjects (age 52.14 ± 7.41 years). Compared with the control group, both native T1 and extracellular volume (ECV) values were significantly increased in the CHD group (P < 0.05). The native T1 value was positively correlated with the ECV value (r = 0.711, P < 0.01). In the LGE+ subgroup, native T1 and ECV values were significantly higher than those in the control group (P < 0.001). The area under the receiver operating characteristic curve (AUC) for native T1 was 0.763. The optimal diagnostic threshold for native T1, as measured by the Picture Archiving and Communication System (PACS), was 1,275.50 ms, with a sensitivity of 93.3% and a specificity of 63.3%.ConclusionsThe diagnostic performance of scanner-generated native T1 Mapping demonstrates robust accuracy and holds potential as a non-invasive tool for evaluating diffuse myocardial fibrosis in patients with CHD.